Cotton in West Africa the economic and social stakes - Organisation for Economic Co-operation and Development; ProQuest (Firm) (Paris : OECD, 2006)
In West Africa, approximately 16 million people depend directly or indirectly on cotton cultivation. Cotton plays a vital role in the economic and social development of many countries, and in improving the livelihoods of the inhabitants. It has also enabled West Africa to become a major player on the international market, since it is now the second largest fiber exporter behind the United States. This success is partly due to an integrated approach which is often called the "cotton system." Since the World Trade Organization's 2003 Ministerial Conference in Cancun, the actors in the international community have recognized the crucial need to address the cotton crisis in an "ambitious, rapid and specific" manner. At the end of the Hong Kong Ministerial Conference in December 2005, progress was made in the negotiations aiming to reduce subsidies, ensure market access and improve development policies. On 24 July, multilateral trade negotiations of the Doha "Development Round" were suspended because an agreement could not be reached which would satisfy both developing and developed countries. This book contends that dialogue between developed and developing countries should continue in order to find a lasting solution to the difficulties facing the cotton sub-sector. It sets out the regional stakes linked to the economic and social importance of cotton in West Africa. It retraces the consultation process on the West African cotton crisis with the aim of finding a negotiated solution acceptable to all parties. Also discussed are the challenges and the measures that need to be taken over the medium and long term in order to prevent this sub-sector's sudden collapse. Countries covered: Benin, Burkina Faso, Cameroon, Cape Verde, Chad, Cote d'Ivoire, The Gambia, Ghana, Guinea, Guinea-Bissau, Liberia, Mali, Mauritania, Niger, Nigeria, Senegal, Sierra Leone, and Togo.--Publisher summary.
The strategic importance of cotton production and trade in West Africa -- Role of cotton in livelihoods and access to services -- West African perspectives : challenges for the cotton sub-sector -- Ten strategic questions for African cotton sub-sector support initiatives to address -- Chronology of key events on cotton in West and Central Africa from 2001 to 2005.
Includes bibliographical references (p. 125-127).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Cotton trade -- Social aspects -- Africa, West; Cotton trade -- Economic aspects -- Africa, West; Textile industry -- Africa, West; Electronic books